Application of AHP, TOPSIS, and TFNs to plant selection for phytoremediation of petroleum-contaminated soils in shale gas and oil fields. (1st October 2019) - Wang, Bing; Xie, Hong-Li; Ren, Hong-Yang; Li, Xi; Chen, Li; Wu, Bai-Chun
Abstract: In order to reduce the cost of phytoremediators selection in phytoremediation on petroleum-contaminated soils, long-term experiments and in-situ trials included, an evaluation system for plant selection in phytroremediaiton was conducted in accordance with two case study, Changning shale gas field and Liaohe oil field. The evaluation system was constructed with two multi-objective decision-making methods, analytic hierarchy process (AHP) and technique for order of preference by similarity to ideal solution (TOPSIS), combined with triangular fuzzy numbers (TFNs). The comprehensive evaluation system was involved with three criteria and nine indexes. The calculated weights indicated that moisture was the most influential factor in the plants selection with the highest weight in both Changning shale gas field and Liaohe oil field. A total of 23 plants from these two study areas were used as alternative plants for phytoremediation and it suggested that Testuca arundinacea might be a suitable plant for the phytoremediation process after determination. Results of sensitivity analysis confirmed that the combination of the fuzzy AHP and TOPSIS in these process was reasonable and practicable. The successful application of fuzzy AHP and TOPSIS, to plant selection for the phytoremediation of petroleum-contaminated soils was also highlighted. The usefulness of the combined application of these two methodologies for decision-makers is anticipated. Such a combination is a convenient and effective approach to the selection of suitable plants for the phytoremediation of petroleum-contaminated soils and it can provide scientific and technological support for decision-makers during the supervision of petroleum-contaminated sites.